The problem of developing a universal definition of private military and security activities - Savka, Oleksandr (Problems of legality, 2026)
The article provides a comprehensive study of the problem of the lack of a unified and generally accepted definition of private military and security activities in the system of international and national law, which negatively affects the effectiveness of legal regulation in the field of security. It analyzes the evolution of scientific approaches to understanding private military and security activities, as well as the provisions of international legal acts, regional documents, and the legislation of individual states that regulate the activities of private military and security companies. The key common and distinctive characteristics of such companies are identified, in particular with regard to the nature of the services provided, the degree of use of armed force, the level of state control, and the legal status of personnel. Particular attention is paid to the reasons for terminological uncertainty, among which the diversity of functional models of private military and security activities, the lack of a unified international legal approach, and the political sensitivity of the issue of delegating state functions in the use of force to private entities are highlighted. The article examines the problems of distinguishing between the concepts of «private military activity», «private security activity», «mercenary activity», and «military support services», which is of fundamental importance for determining the scope of rights and obligations of the relevant entities. The article also analyzes the legal, security, and ethical challenges associated with the activities of private military and security companies, in particular the issue of responsibility for violations of international humanitarian law and human rights, mechanisms for holding the personnel of such companies accountable, as well as issues of transparency, accountability, and democratic civilian control. It justifies the need to develop a universal definition of private military and security activities as a conceptual basis for improving national legislation, harmonizing international legal standards, and creating an effective system of international control in the field of security privatization.